Effect of Fertilization with Ash from Biomass Combustion on the Fatty Acid Composition of Winter Rapeseed Oil - Ewa Szpunar-Krok; Anna Wondołowska-Grabowska (Agronomy)
Bioenergy production generates huge amounts of ash from biomass combustion. One of the attempts to utilize them is to use them in agriculture as fertilizers. The response to this challenge is a three-year field experiment (2018–2021) where the effect of fertilization with ash from forest biomass (approx. 70%) and agricultural biomass (approx. 30%), and soil type (Gleyic Chernozem and Haplic Luvisol), on the fatty acid (FA) profile of winter rape seeds (Brassica napus L. ssp. oleifera Metzg) was studied. Environmental factors modified the accumulation of fatty acids in winter oilseed rape seeds to the greatest extent and included all labelled unsaturated and saturated fatty acids from C12:0 to C24:0, with exceptions. In warm and dry years, C18:1n9c, C18:2n9c and C18:3n6 accumulated more, while cooler and humid years promoted an increase in the content of, among others, C20:2, C24:1, C18:3n3, C20:4 and C22:2. Cultivation of plants in Gleyic Chernozem soil promoted the accumulation of unsaturated fatty acids C18:3n3 and C18:3n6 in winter rape seeds—important from the nutritional point of view. The soil type Haplic Luvisol influenced a larger number of saturated acids and promoted an increase in their content to a greater extent than the Gleyic Chernozem soil type. Among unsaturated fatty acids, fertilization had an effect only on C18:3n3 with mineral fertilization (variant D1) and a very high K dose (variant D5) and C24:1 with the highest K dose (variant D6). No negative changes in the proportions of FAs, including omega-3 and omega-6, were demonstrated under the influence of BA application.